PEMBELAJARAN MATEMATIKA BERORIENTASI HIGHER ORDER THINKING SKILLS - Nenden Chiarun Nisa (LPPM Universitas Bina Bangsa, 2023)
Higher Order Thinking Skills or HOTS is one of the abilities demanded in the 21st century that is very important to be applied in student learning in class. In this literature review discussed the the effectiveness of HOTS learning, the difficulties of students and teachers in HOTS learning and how HOTS learning in Mathematics. The results show that HOTS learning can improve student achievement and motivation but on the other hand there are still many teachers who do not fully understand HOTS learning itself. Teachers must have good learning design skills to get meaningful learning activity so the students getting used to HOTS. Getting used to HOTS on students cannot be done suddenly so HOTS learning can be started simply to a more complex level.